2002
DOI: 10.1029/2001ja009233
|View full text |Cite
|
Sign up to set email alerts
|

Electron and proton excitation of the FUV aurora: Simultaneous IMAGE and NOAA observations

Abstract: [1] The Far Ultraviolet (FUV) imaging system on board the IMAGE satellite provides a global view of the north auroral region in different spectral channels. The Wideband Imaging Camera (WIC) is sensitive to the N 2 LBH emission and NI emissions produced by both electron and proton precipitations. The SI12 camera images the Lyman-a emission due to incident protons only. We compare WIC and SI12 observations with model predictions based on particle measurements from the TED and the MEPED detectors on board NOAA-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(70 citation statements)
references
References 27 publications
4
66
0
Order By: Relevance
“…The comparison was made for both WIC and SI12 data. Taking into consideration all possible sources of error, WIC observations showed agreement with in situ induced auroral brightness within 70%, but SI12 observations coupled with simulation from the Monte Carlo code predicted proton fluxes twice as large as the in situ measurements (Coumans et al, 2002). Consequently, in this work, the proton energy fluxes are adjusted by a factor of 2 to account for this overestimate of the SI12 derived proton flux.…”
Section: The Fuv Imagers and The Auroral Precipitationmentioning
confidence: 99%
See 3 more Smart Citations
“…The comparison was made for both WIC and SI12 data. Taking into consideration all possible sources of error, WIC observations showed agreement with in situ induced auroral brightness within 70%, but SI12 observations coupled with simulation from the Monte Carlo code predicted proton fluxes twice as large as the in situ measurements (Coumans et al, 2002). Consequently, in this work, the proton energy fluxes are adjusted by a factor of 2 to account for this overestimate of the SI12 derived proton flux.…”
Section: The Fuv Imagers and The Auroral Precipitationmentioning
confidence: 99%
“…This discrepancy was tentatively attributed to highenergy protons above the 30 keV upper limit of the detectors, suggesting that higher energy protons could be important in producing this emission. Coumans et al (2002) used in situ particle measurements from NOAA-15 and NOAA-16 satellites to check this possibility and assess the role of proton excitation of FUV emissions. The NOAA sets of detectors offers the advantage of observing electrons in the energy range 50 eV-1000 keV and protons from 50 eV to 800 keV, including all relevant auroral energies.…”
Section: The Fuv Imagers and The Auroral Precipitationmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparison with the Ly-α emission extracted along the satellite track from SI12 images showed good agreement with the peak value at the center of the proton arc , although the latitudinally integrated brightness may underestimate the observations by up to a factor of 2. Coumans et al (2002) have shown that protons with energies above 30 keV, the upper limit of the DMSP and FAST particle detectors, may play a significant role in the excitation of the equatorward regions of the proton aurora, particularly in the afternoon sector.…”
Section: Introductionmentioning
confidence: 99%